Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3113/fai.2010.0348
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Technique for Combined Anterior, Lateral, and Posterior Ankle and Hindfoot Procedures: Technique Tip

Abstract: Level of Evidence: V, Expert Opinion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Theoretically, changing the patient's set‐up from the prone to the supine position or vice versa would prolong the operative time and would carry the potential risk of contamination of the arthroscopic instruments and consequently increase the overall risk of infection [18]. It was such possible hazards that lead several articles to be focused mainly on the technical tips of performing such combined arthroscopic manoeuvres without the need for re‐positioning of the patient [1, 2, 14, 18, 23]. There have been a few published reports on posterior ankle arthroscopy in which the authors found it necessary to perform an anterior arthroscopy for additional anterior ankle pathology [6, 12, 27, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, changing the patient's set‐up from the prone to the supine position or vice versa would prolong the operative time and would carry the potential risk of contamination of the arthroscopic instruments and consequently increase the overall risk of infection [18]. It was such possible hazards that lead several articles to be focused mainly on the technical tips of performing such combined arthroscopic manoeuvres without the need for re‐positioning of the patient [1, 2, 14, 18, 23]. There have been a few published reports on posterior ankle arthroscopy in which the authors found it necessary to perform an anterior arthroscopy for additional anterior ankle pathology [6, 12, 27, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The originally described management protocol involved utilization of an anterior ankle arthroscopy combined with a posterior ankle arthrotomy [15]. More recently, there have been few manuscripts that technically describe positioning manoeuvres during the proposed simultaneous management of these concurrent anterior and posterior pathologies [2, 14, 23]. There have been very few reports, however, that actually describe the application of concomitant arthroscopic measures on a case series studies of patients with simultaneous anterior and posterior ankle pathologies [3, 4, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The lateral decubitus position can afford access to the anterior, lateral, and posterior ankle. 19 A beanbag is used for stability, an axillary role is placed, and all bony prominences are well padded. The hip is abducted, the knee is flexed, and then the knee is placed in an arthroscopic knee holder to support the thigh for the anterior ankle arthroscopy.…”
Section: Pitfallsmentioning
confidence: 99%
“…6 Before lateral ligament reconstruction, evaluation of the joint first by ankle arthroscopy has been useful to find secondary pathology that may be contributing to ankle symptoms. 19 Associated pathology can include intra-articular pathology (chondral lesions, loose bodies, ossicles, synovitis, and arthrosis), impingement lesions (anterior and anterolateral), and other instabilities other than lateral (subtalar, syndesmotic, and medial). 11 Hinterman and colleagues 20 found that intra-articular pathology, a chondral lesion of the talus specifically, was found arthroscopically in more than 50% of cases, whereas the preoperative diagnosis was made in only 4% of patients.…”
mentioning
confidence: 99%